INDEKS KEPUASAN PASIEN TERHADAP PELAYANAN RUMAH SAKIT UMUM DAERAH (RSUD) KABUPATEN POLEWALI MANDAR - Wahdania Wahdania; Djuliati Saleh; Fatmawati Fatmawati (Department of Public Administration, Muhammadiyah University of Makassar, 2015)
The research aims to gain an overview of Community Satisfaction Index (HPI) to service the Regional General Hospital (Hospital) at Polewali Mandar. The research method is descriptive quantitative. The data collection had been using a questionnaire by selecting respondents with accidental sampling technique. The Data collected from a questionnaire distributed to respondents and then analyzed using community satisfaction index (HPI), which is information about the level of community satisfaction obtained from the quantitative data measurement. The result showed that the Community Satisfaction Index for each service element Regional General Hospital (Hospital) at Polewali Mandar was 68.93. If the value is included in the table IKM conversion interval value, then the result of the assessment is